2006
DOI: 10.1111/j.1442-9993.2006.01605.x
|View full text |Cite
|
Sign up to set email alerts
|

Stream salinization is associated with reduced taxonomic, but not functional diversity in a riparian plant community

Abstract: Dryland salinity presents an overwhelming threat to terrestrial and aquatic habitats in Australia, and yet there remains very little empirical evidence of the impacts of secondary salinization on the biodiversity of riparian communities. Here we describe the response of a riparian plant community to stream and soil salinization, 25 years after the experimental clearing of a catchment in south-western Australia. Riparian plant species diversity was inversely related to soil salinity, and plant species compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Nevertheless, we found secondary salinization was signiÞcantly associated with changes in the composition of the habitat of water bodies. Our study supports others, which have found relationships between terrestrial, riparian, and aquatic vegetation and salinity (Cramer and Hobbs 2002;Davis et al 2003;Lymbery et al 2003;Pinder et al 2004Pinder et al , 2005Strehlow et al 2005;Doupé et al 2006;Seddon et al 2007), such as the replacement of grasses and rushes, in fresh water areas, with salt tolerant succulents such as Sarcocornia sp. in saline areas (Lymbery et al 2003).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, we found secondary salinization was signiÞcantly associated with changes in the composition of the habitat of water bodies. Our study supports others, which have found relationships between terrestrial, riparian, and aquatic vegetation and salinity (Cramer and Hobbs 2002;Davis et al 2003;Lymbery et al 2003;Pinder et al 2004Pinder et al , 2005Strehlow et al 2005;Doupé et al 2006;Seddon et al 2007), such as the replacement of grasses and rushes, in fresh water areas, with salt tolerant succulents such as Sarcocornia sp. in saline areas (Lymbery et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…As water bodies become saline, there are direct physiological effects on biota (Patrick and Bradley 2000, James et al 2003, Hassell et al 2006. Habitat in secondary salinized ecosystems is simpliÞed, and both salinity and habitat are likely to have a cumulative effect on the occurrence of other organisms (Davis et al 2003, Doupé et al 2006, Lyons et al 2007). Our study has found both direct (salinityÐmos-quito) and indirect (salinityÐ environment/habitatÐ mosquito) associations between the disturbance of secondary salinization and the abundance of mosquitoes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations